A new strategy for dissimilar material joining between SiC and Al alloys through use of high-Si Al alloys - Yang, Yongjing (2022)
Joining metals and ceramics plays a crucial role in many engineering applications. The current research aims to develop a simple and convenient approach for dissimilar material joining between SiC and Al alloys. In this work, Al alloys with Si contents varying from 7 wt.% to 50 wt.% were bonded with SiC at a high temperature of 1100◦C by a pressure-less bonding process in a vacuum furnace, and shear tests were carried out to study the bonding strength. When using low-Si Al alloys to bond with SiC, the bonding strength was very low. The bonding strength of Al/SiC joints increased significantly through the use of high-Si Al alloys with 30 wt.% and 50 wt.% Si. The shear strength achieved (28.8 MPa) is far higher than those reported previously. The remarkable improvement in bonding strength is attributed to the suppression of brittle interfacial products and reduced thermal stresses. This research provides a new strategy for joining between SiC and a wide range of Al alloys through the use of high-Si Al alloys as the interlayers.